Prognostic significance of microsatellite-instability in gastric and gastroesophageal junction cancer patients undergoing neoadjuvant chemotherapy - Haag, Georg Martin; Busch, Elena; Ahadova, Aysel; Schmidt, Thomas; Peters, Leila; Blank, Susanne; Heger, Ulrike; Apostolidis, Leonidas; Berger, Anne Katrin; Springfeld, Christoph; Lasitschka, Felix; Jäger, Dirk; et al. (International journal of cancer, 2019)
Perioperative systemic treatment is standard of care for Caucasian patients with locally advanced, resectable gastric adenocarcinoma. The prognostic relevance of the microsatellite instability (MSI) status in patients undergoing neoadjuvant chemotherapy followed by resection is unclear. We analyzed the association of the MSI status with histological regression and clinical outcome in patients undergoing neoadjuvant systemic treatment. Tumor tissue from patients undergoing neoadjuvant chemotherapy followed by resection for gastric or gastroesophageal-junction adenocarcinoma was analyzed for MSI status using a mononucleotide marker panel encompassing the markers BAT25, BAT26, and CAT25. Histological regression, relapse-free survival and overall survival were calculated and correlated with MSI status. We identified the MSI-H phenotype in 9 (8.9%) out of 101 analyzed tumors. Though a poor histological response was observed in eight out of nine MSI-H patients, overall survival was significantly better for patients with MSI-H compared to MSS tumors (median overall survival not reached vs. 38.6 months, log-rank test p = 0.014). Among MSI-H patients, an unexpected long-term survival after relapse was observed. Our data indicate that the MSI-H phenotype is a favorable prognostic marker in gastric cancer patients undergoing neoadjuvant treatment. The benefit of perioperative cytotoxic treatment in patients with MSI-H gastric cancer, however, remains questionable. Future trials should stratify patients according to their MSI status, and novel treatment modalities focusing on MSI-H tumors should be considered.
Online 29 Nov 2018
Gesehen am 07.08.2019